Сross-flows of air and stack gases in the gaps of regenerative air heater - Kozlokov, Aleksandr Jur'evich; Stennikov, Viktor Nikolayevich; Goloshchapov, Vladimir; Kasilov, Viktor Iosifovich; Kasilov, Oleg (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The cross- flows of air and emitted gases that occur in the regenerative air heater (RAH) in the case of unsatisfactory adjustment of seals result in a reduction of the efficient operation of the boiler unit. Seal clearances put up the main resistance to the air cross-flows and this allowed us to present the hydraulic circuit of rotor seals for the RAH. To define the cross-flows we assumed that the power unit operates at nominal operating conditions. To define the geometric characteristics of the RAH we calculated the cross area of seal gaps. When the rotor and the regenerative air heater casing are exposed to thermal stresses a nonuniform circumferential change in peripheral and axial clearances will be observed during their cyclic heating and cooling. A method of mass balances was used as the computation model. Appropriate methods were developed to define the above change during the RAH operation and the cross-flows were estimated for the specified value of seal clearances. The experience gained in the RAH operation showed that the air cross –flows may reach ~ 30 % and higher in the case of insufficiently precise regulation. The main values of the cross-flow of air and heating emitted gases are observed in radial seals. Therefore, the attention should be paid to the precise regulation of the seals and the development of the methods used for the control of seal clearances during the hot-state RAH operation.